An Ethnographic Study of Health Information Technology Use in Three Intensive Care Units. (25th January 2017) - Leslie, Myles; Paradis, Elise; Gropper, Michael A.; Kitto, Simon; Reeves, Scott; Pronovost, Peter
Abstract : Objectives: To identify the impact of a full suite of health information technology (HIT) on the relationships that support safety and quality among intensive care unit (ICU) clinicians. Data Sources: A year‐long comparative ethnographic study of three academic ICUs was carried out. A total of 446 hours of observational data was collected in the form of field notes. A subset of these observations—134 hours—was devoted to job‐shadowing individual clinicians and conducting a time study of their HIT usage. Principal Findings: Significant variation in HIT implementation rates and usage was noted. Average HIT use on the two "high‐use" ICUs was 49 percent. On the "low‐use" ICU, it was 10 percent. Clinicians on the high‐use ICUs experienced "silo" effects with potential safety and quality implications. HIT work was associated with spatial, data, and social silos that separated ICU clinicians from one another and their patients. Situational awareness, communication, and patient satisfaction were negatively affected by this siloing. Conclusions: HIT has the potential to accentuate social and professional divisions as clinical communications shift from being in‐person to electronically mediated. Socio‐technically informed usability testing is recommended for those hospitals that have yet to implement HIT. For those hospitals already implementing HIT, we suggest rapid, locally driven qualitative assessments focused on developing solutions to identified gaps between HIT usage patterns and organizational quality goals.